2013
DOI: 10.1002/rrq.52
|View full text |Cite
|
Sign up to set email alerts
|

Reading Amount as a Mediator of the Effects of Intrinsic and Extrinsic Reading Motivation on Reading Comprehension

Abstract: This study examined the role of reading amount as a mediator of the effects of intrinsic and extrinsic reading motivation on higher order reading comprehension (comprised of paragraph‐ and passage‐level comprehension) in a sample of 159 fifth‐grade elementary students. A positive association between intrinsic reading motivation and reading amount was assumed, whereas a negative contribution to reading amount was expected for extrinsic reading motivation. As control variables, lower order reading comprehension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
173
2
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(219 citation statements)
references
References 67 publications
24
173
2
20
Order By: Relevance
“…Prior studies confirmed the factorial validity of the RMQ (Schaffner & Schiefele, 2007;Schaffner, Schiefele, & Schmidt, 2013;Schaffner, Schiefele, & Ulferts, 2013). They also demonstrated that the different dimensions capture two higher-order factors: intrinsic reading motivation (interest and involvement) and extrinsic reading motivation (competence, competition, and social recognition).…”
Section: Reading Motivationmentioning
confidence: 72%
See 1 more Smart Citation
“…Prior studies confirmed the factorial validity of the RMQ (Schaffner & Schiefele, 2007;Schaffner, Schiefele, & Schmidt, 2013;Schaffner, Schiefele, & Ulferts, 2013). They also demonstrated that the different dimensions capture two higher-order factors: intrinsic reading motivation (interest and involvement) and extrinsic reading motivation (competence, competition, and social recognition).…”
Section: Reading Motivationmentioning
confidence: 72%
“…Specifically, the participants were asked (a) how many books they have read during the last 12 months (1 = no book at all, 2 = 1 to 5 books, 3 = 6 to 10 books, 4 = 11 to 20 books, 5 = more than 20 books), (b) how long they usually read in a book without making a break (1 = 5 min, 2 = 15 min, 3 = 30 min, 4 = 60 min, 5 = more than 60 min), and (c) how often they read in their spare time (1 = about once a month, 2 = about once a week, 3 = several times in the week, 4 = daily, 5 = several times during the day). The validity of the scale is supported by significant positive associations with intrinsic reading motivation, reading comprehension, and different aspects of the home literacy environment (Schaffner, Schiefele, & Schmidt, 2013;Schaffner, Schiefele, & Ulferts, 2013).…”
Section: Reading Amountmentioning
confidence: 92%
“…Researchers who had spotlighted on motivation had discussed about the roles of cognitive and motivation alternatives interaction and the impact of variables on learners achievement. Moreover, recent studies focused on the developing of cognitive skills and vivacious activities to enhance learners reading motivation (Schaffner & Ulferts, 2013). Some of these studies had examined intrinsic motivation as a predictor of progress in several regions, such as reading, sports, and mathematics.…”
Section: Email: Info@ijreeonlinecommentioning
confidence: 99%
“…This suggests that students' completion of comprehension workbooks prepared them to achieve on standardized tests, and thus that workbook completion serves as an adequate proxy for literacy gains. Furthermore, significant research has demonstrated that amount of reading is associated with reading achievement (e.g., Allington, 2012;Guthrie & McRae, 2012;Schaffner, Schiefele, & Ulferts, 2013). Therefore, it seems plausible that the associations between teachers' fidelity of implementation and students' workbook completion and number of words read suggest a relationship between FoI and student achievement on a larger scale, and that over time, the variation in FoI described in this study will contribute to differences in students' achievement in comprehension and fluency.…”
Section: Coaching Implementation and Outcomesmentioning
confidence: 99%